Disease Activity in Graves' Ophthalmopathy: Diagnosis with Orbital MR Imaging and Correlation with Clinical Score. Issue 5 (October 2013) - Tortora, Fabio; Cirillo, Mario; Ferrara, Marco; Belfiore, Maria Paola; Carella, Carlo; Caranci, Ferdinando; Cirillo, Sossio
In Graves' ophthalmopathy (GO) it is important to distinguish acute inflammation at an early stage, responsive to immunosuppressive treatment, from inactive fibrotic end stage disease, unresponsive to the same treatment. The purpose of this study was to identify the most relevant signal intensities on orbital MR imaging with contrast administration both to classify patients according to their clinical activity score (defined by a cut-off value of 3) and to make a prediction of patient's CAS. Such threshold was considered as widely used in literature. Sixteen consecutive patients with a diagnosis of GO in different phases of thyroid disease based on clinical and orbital MR imaging signs, and six normal volunteers were examined. Orbital MR imaging was performed on a 1.5 Tesla MR Unit. MR scans were assessed by an experienced neuroradiologist, blinded to the clinical examinations. We found a statistical correlation between CAS and both STIR and contrast enhanced T1-weighted sequences. There was also a statistically significant correlation between STIR and contrast-enhanced T1 images disclosing the possibility of avoiding the injection of contrast medium. Our study proved that signal intensity values on STIR sequence increase in the inflammatory oedematous phase of disease. We confirmed the correlation between signal intensities on this sequence and CAS, showing an increase in signal intensity proportional to the CAS value. So we validated MRI use to establish the activity phase of disease more sensitively than CAS alone.